Fringe Benefits to Cash Collateral as a Social Guarantee of Police Rights during Quarantine in Ukraine (Law and Safety, 2020)
The peculiarities of the legal regulation for establishing and paying fringe benefits to the cash collateral during quarantine for police officers have been studied. The normatively defined grounds for fringe benefits and the actual substantiation of the application of such payments for police officers have been analyzed. The legal position of the need for fringe benefits for all police officers has been substantiated, based on the tasks facing the National Police and the provision of police services to the population of Ukraine.A comprehensive understanding of the tasks of the National Police allows us to conclude that the exercise of police powers is carried out through the provision of police services, which involves direct contact of police officers with the public or individual citizens. Under such conditions, the only possible conclusion is that every police officer during quarantine is entitled to fringe benefits to the cash collateral.Social guarantees for police officers, which are defined by the highest regulatory act according to legal force, should not be narrowed and limited to bylaws that have lower legal force. Additional social guarantees for police officers during quarantine are determined not so much by their status as by the tasks and functions that police officers continue to perform in society, providing police services to society and its individual members without being able to take advantage of additional guarantees provided by the state to the citizens, the whole population in order to save their lives and health from coronavirus infection.Reducing the level of social guarantees by depriving police officers of fringe benefits for providing police services during quarantine causes different status of police officers, which is mainly stipulated not to objective factors, but only subjective, and also affects the efficiency of police services and security of police officers.
Keywords: quarantine; police; fringe benefits; cash collateral; police services; law and order; life sustenance